2023
DOI: 10.3390/jof9020220
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pneumocystis and Morphological Description of Fungal Distribution and Severity of Infection in Thirty-Six Mammal Species

Abstract: Pneumocystis spp. are thought to adapt to the lungs of potentially all mammals. However, the full host range, fungal burden and severity of infection are unknown for many species. In this study, lung tissue samples originating from 845 animals of 31 different families of eight mammal orders were screened by in situ hybridization (ISH) using a universal 18S rRNA probe for Pneumocystis, followed by hematoxylin and eosin (H&E) staining for determining histopathological lesions. A total of 216 (26%) samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(49 citation statements)
references
References 88 publications
0
49
0
Order By: Relevance
“…The size of the colonized healthy population is expected to be substantially larger than that of the colonized immunodeficient population; this hypothesis is potentially supported by the immune evasion mechanism associated with the large major surface glycoprotein family, which is thought to be operative in immunocompetent hosts [ 356 , 357 ]. Nonetheless, it remains uncertain if colonization in some cases, especially in the early stage, may represent subclinical or self-limited infection, as studies of Pneumocystis -infected healthy animals have demonstrated mild pathological changes in the lungs [ 358 , 359 ]. Distinguishing between subclinical infection and colonization as well as latency discussed below is difficult based on the current data, and it may also depend on how these terms are defined, particularly in terms of the level of damage to the host and the host immune response, as discussed for other pathogens [ 360 ].…”
Section: Pneumocystis Colonizationmentioning
confidence: 99%
“…The size of the colonized healthy population is expected to be substantially larger than that of the colonized immunodeficient population; this hypothesis is potentially supported by the immune evasion mechanism associated with the large major surface glycoprotein family, which is thought to be operative in immunocompetent hosts [ 356 , 357 ]. Nonetheless, it remains uncertain if colonization in some cases, especially in the early stage, may represent subclinical or self-limited infection, as studies of Pneumocystis -infected healthy animals have demonstrated mild pathological changes in the lungs [ 358 , 359 ]. Distinguishing between subclinical infection and colonization as well as latency discussed below is difficult based on the current data, and it may also depend on how these terms are defined, particularly in terms of the level of damage to the host and the host immune response, as discussed for other pathogens [ 360 ].…”
Section: Pneumocystis Colonizationmentioning
confidence: 99%
“…Antilope cervicapra (blackbuck) [6], Antilope spp. (antelope) [7], Bos bonasus (bison) [6,7], Bos taurus (cattle) [6,[8][9][10][11], Bubalus bubalis (water buffalo) [6], Capra hircus (goat) [6,8,[11][12][13], Hippotragus niger (sable antelope) [14], Ovis aries (sheep) [6,7,11], Rupicapra rupicapra (chamois) [6] Camelidae (camelids) Camelus bactrianus (Bactrian camel) [6], Camelus dromedarius (Arabian camel) [6], Lama glama (llama) [6,15], Vicugna pacos (alpaca) [6] Cervidae (deer)…”
Section: Order Family Speciesmentioning
confidence: 99%
“…Capreolus capreolus (Western roe deer) [6,16], Cervus alfredi (Visayan spotted deer) [6], Cervus elaphus (red deer) [6], Cervus nippon (Sika deer) [6], Cervus spp. (deer) [6,9], Dama dama (European fallow deer) [11], Elaphurus davidianus (Pere David's deer) [6], Muntiacus muntjak (Indian muntjac) [7], Rangifer tarandus (reindeer) [6], Rangifer tarandus groenlandicus (caribou) [16], Rusa unicolor (sambar) [7] Suidae (swine)…”
Section: Order Family Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 A few cases of Pneumocystis pneumonia have been described and reviewed in goats, compared to cattle, sheep, and other mammals. 40 Blastomycosis with dermatophilosis has been described in Nigeria. 4 Exserohilum rostratum , a dematiaceous fungus, plant pathogen, and cause of an outbreak of fungal meningitis in people associated with contaminated methylprednisolone injections, 35 has been reported as a cause of rhinitis in a goat in Brazil.…”
mentioning
confidence: 99%